Evaluation of thyroid function tests and thyroid autoantibodies in female patients with Hepatitis C - Etem, Arzu Akagac; Baran, Irmak; Etem, Ebru (Bayrakol Medical Publisher, 2021)
Aim: The prevalence of hepatitis C virus infection in the world is estimated to be approximately 2,2-3%. In our country, the anti-HCV antibody positivity rate obtained from donor screenings in different centers was found to be 0,54% on average between 2000-2006, while in the community-based studies, the anti-HCV positivity rate was found between 0,4-2,1%. In this study, it was aimed to investigate the diagnosis of the thyroid gland in patients with HCV infection in Usak province, disorders of thyroid function tests, and the frequency of thyroid autoantibodies. Materials and Methods: Fifty-seven anti-HCV positive female patients who applied to Private Oztan Health Hospital between January 1, 2016 and December 31,.2018 were retrospectively evaluated and included in the study. Since there were only 4 male patients, female patients were included in the study. The laboratory results of the patients were reached from the laboratory information system. Anti-HCV antibody was studied with original reagent and calibrators on Vitros ECI/ECIQ Immunodiagnostic Systems USA. Values above 1 mIU/mL were considered positive. Free T3, free T4, TSH, anti-TG, anti-TPO, AST, and ALT results were compared statistically in both groups. Results: There was a significant difference between ALT levels and the Student t-test, which compared the means across the two groups (p=0,0). With the use of the Pearson Chi-Square test, a statistically significant difference was found in Free T3, Free T4, Anti-TG, Anti-TPO, thyroid-related disease diagnosis, and diagnosis and/or thyroid test dysfunction parameters (p<0,05). Discussion: Female patients with HCV infection have a high risk of diseases related to the thyroid-gland. Therefore, these patients should be examined and monitored for thyroid gland disease, thyroid tests dysfunction, and thyroid autoantibodies. We believe that it is beneficial to carry out clinical research along with treatment follow-ups and also in the group of HCV infected male patients.
Keywords: Hepatitis C; Thyroid gland; Thyroid tests